Healthy minds index, Spanish version of core dimensions of wellbeing - Humberto Charles-Leija; Tammi R. A. Kral; Raquel Tatar; Richard J. Davidson; Carlos G. Castro; Rosalinda Ballesteros-Valdés; Masaya Okamoto (PLoS ONE, 2025)
Psychological wellbeing is a crucial aspect of human flourishing, yet validated assessment tools are needed across diverse linguistic and cultural contexts. This study aimed to adapt and validate the Healthy Minds Index (HMx) for Spanish-speaking populations (HMx-SV). The HMx-SV assesses four core dimensions of wellbeing: awareness, connection, insight, and purpose. We conducted exploratory and confirmatory factor analyses on data from two independent samples of university students (N = 362 and N = 1,594). The findings confirmed a four-factor structure, with strong internal consistency and convergent validity with established wellbeing measures. The HMx-SV demonstrated robust psychometric properties, making it a reliable and valid tool for assessing wellbeing in Spanish-speaking populations. By expanding access to a culturally adapted instrument, this study contributes to the broader understanding and promotion of psychological wellbeing in diverse communities.